Effect of Principal Supervision on Teacher Pedagogic Competencies - Aswinda Aswinda; Arifuddin Siraj; Saprin Saprin (Jurnal Ilmiah Ilmu Administrasi Publik, 2019)
The research aims to Effect of Principal Supervision on Teacher Pedagogic Competencies at Public Elementary School 237 Aletellue in Soppeng Regency.This research use quantitative methodology with correlational ex post facto design to explain the research questions. To understand the issue, this research use methodological approach (quantitative-positivistic) and scientific approach (pedagogic and psychological). The participants of this reseach are 13 teachers at Publich Elementary School 237 Aletellue. The data were gathered using survey and dokumentasi, and then analysed through descriptive statistic with hypothesis testing using correlation and linear regression coefficient. The research reveals some key findings. The first finding shows that the supervision of principals shows a comparison of the competence of pedagogic teachers. This, seen from every activity of the teacher who is able to be effective in improving the competencies possessed. Helps develop science with innovation and creativity.